Effects of treatment on the characterization of organic matter in wastewater: a review on size distribution and structural fractionation - GÜRSOY HAKSEVENLER, BETÜL HANDE (My University, 2020)
Abstract Since it is difficult to analyze the components of organic matter in complex effluent matrices individually, the use of more collective, but at the same time, specific wastewater characterization methods would be more appropriate to evaluate changes in effluent characteristics during wastewater treatment. For this purpose, size distribution and structural (resin) fractionation tools have recently been proposed to categorize wastewater. There are several case studies available in the scientific literature being devoted to the application of these fractionation methods. This paper aimed to review the most relevant studies dealing with the evaluation of changes in wastewater characteristics using size distribution and structural (resin) fractionation tools. According to these studies, sequential filtration-ultrafiltration procedures, as well as XAD resins, are frequently employed for size and structural fractionations, respectively. This review focuses on the most relevant publications including biological treatment processes, as well as chemical treatment methods such as coagulation-flocculation, electrocoagulation, the Fenton's reagent and ozonation. This study aims at providing an insight into the possible treatment mechanisms and details the understanding what structural features of wastewater components enabled or prevented efficient treatment (removal) or targeted pollutants.
Effects of treatment on the characterization of organic matter in wastewater